2021
DOI: 10.1097/j.pain.0000000000002357
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive therapy, mindfulness-based stress reduction, and behavior therapy for the treatment of chronic pain: randomized controlled trial

Abstract: Trials of cognitive therapy (CT), mindfulness-based stress reduction (MBSR), and behavior therapy (BT) suggest that all 3 treatments produce reductions in pain and improvements in physical function, mood, and sleep disturbance in people with chronic pain conditions. Fewer studies have compared the relative efficacies of these treatments. In this randomized controlled study, we compared CT, MBSR, BT, and treatment as usual (TAU) in a sample of people with chronic low back pain (N 5 521). Eight individual sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 47 publications
6
27
0
1
Order By: Relevance
“…For full details regarding participants, including the Consolidated Standards of Reporting of Trials flowchart, see the report by Burns et al (2022) regarding different outcomes across treatments. In brief, participants were recruited through referrals from staff at the Rush University Pain Center, Midwest Orthopedic Clinic and Neurosurgery Clinic at Rush University, and at Clinics at the Duke University Medical Center (e.g., Duke Pain Clinic, Spine Clinic, Neurosurgery Clinic, and Orthopedic Clinic).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For full details regarding participants, including the Consolidated Standards of Reporting of Trials flowchart, see the report by Burns et al (2022) regarding different outcomes across treatments. In brief, participants were recruited through referrals from staff at the Rush University Pain Center, Midwest Orthopedic Clinic and Neurosurgery Clinic at Rush University, and at Clinics at the Duke University Medical Center (e.g., Duke Pain Clinic, Spine Clinic, Neurosurgery Clinic, and Orthopedic Clinic).…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated effects of treatments on three outcome domains: pain interference (primary outcome), pain intensity, and depressive symptoms (secondary outcomes). See Burns et al (2022) for details. The Pain Interference Subscale of the Multidimensional Pain inventory (Kerns et al, 1985) assessed interference with general functioning due to pain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fallbeispiel profitierte zwar von ihrem Kurs und auch von der regelmäßigen Übungspraxis, ist jedoch durch ihre schweren, teils degenerativ bedingten Beschwerden und private Belastungen so deutlich eingeschränkt, dass Effekte eher begrenzt bleiben. Diese „Begrenztheit“ der Methoden ist oft das Ergebnis von Studien 5 , 8 , 16 und wurde im Rahmen der Aktualisierung der Fibromyalgie-S3-Leitlinie im Jahr 2017 kritisch beleuchtet 17 , 18 . Die 2.…”
Section: Zur Praxisunclassified
“…Participation in such programs has shown to be effective to improve anxiety, depression and pain [24][25][26]. Burns et al have shown in patients with chronic pain that MBSR has produced significant differences to the "usual care alone" on average by session 6 [27]. The positive effect of the MBSR program on depression symptoms could be mediated by the reduction in rumination [25].…”
Section: Introductionmentioning
confidence: 99%